2016
DOI: 10.1002/tea.21328
|View full text |Cite
|
Sign up to set email alerts
|

The GAENE—Generalized Acceptance of EvolutioN Evaluation: Development of a new measure of evolution acceptance

Abstract: The present study reports the development of a brief, quantitative, web-based, psychometrically sound measure-the Generalized Acceptance of EvolutioN Evaluation (GAENE, pronounced "gene") in a format that is useful in large and small groups, in research, and in classroom settings. The measure was designed to measure only evolution acceptance-not related knowledge or religious beliefs. Item development was based on extensive student interviews and pretesting followed by multiple rounds of qualitative review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
147
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(151 citation statements)
references
References 54 publications
0
147
3
Order By: Relevance
“…Nadelson and Southerland () suggested further research that uses multiple measures of evolution acceptance. Addressing these concerns, Smith, Snyder, and Devereaux () have developed the GAENE (Generalized Acceptance of EvolutioN Evaluation) that measures evolution acceptance without conflation with evolution knowledge or religious beliefs. Unfortunately, this instrument was not available at the time of data collection for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Nadelson and Southerland () suggested further research that uses multiple measures of evolution acceptance. Addressing these concerns, Smith, Snyder, and Devereaux () have developed the GAENE (Generalized Acceptance of EvolutioN Evaluation) that measures evolution acceptance without conflation with evolution knowledge or religious beliefs. Unfortunately, this instrument was not available at the time of data collection for this study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to widespread difficulty in, and lack of, understanding regarding evolutionary biology, low rates of acceptance of evolution have been reported in the general population (Miller et al 2006;Gallup 2016), in pre-service educators (Romine et al 2016), high school biology educators (Moore and Kraemer 2005;Moore and Cotner 2009;Glaze and Goldston 2015), university professors (Romine et al 2016), and in various student populations (Rice et al 2011;Romine et al 2016). Although belief and acceptance may be closely related, recent investigators of evolution acceptance have separated these constructs, with acceptance being more closely related to "believing that" rather than "believing in" (Smith et al 2016(Smith et al , pp. 1291(Smith et al -1292, and that acceptance "…is more voluntary than belief, and involves a commitment to use what is accepted; belief is less voluntary, and need not be used as a basis for inference or action. "…”
Section: Acceptance Of Evolutionmentioning
confidence: 99%
“…Of the three measures of evolution acceptance, the Measure of Acceptance of the Theory of Evolution (MATE) 10,28 is the oldest and most widely used. The Inventory of Student Evolution Acceptance (I-SEA) 29 and Generalized Acceptance of EvolutioN Evalution (GAENE) 30 tools were more recently developed to address concerns with the MATE, and have gained some traction in the evolution education literature as robust measures. A recent study that employed more than one instrument found the correlation between measures may be quite strong 31 .…”
mentioning
confidence: 99%